2003
DOI: 10.1161/01.cir.0000068340.96506.0f
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Administration of Mineralocorticoid Receptor Antagonist Spironolactone Prevents Post-Infarct Left Ventricular Remodeling Associated With Suppression of a Marker of Myocardial Collagen Synthesis in Patients With First Anterior Acute Myocardial Infarction

Abstract: Background-Aldosterone (ALD) has been shown to stimulate cardiac collagen synthesis and fibroblast proliferation via activation of local mineralocorticoid receptors. In patients with acute myocardial infarction, we demonstrated that ALD was extracted through the infarct heart and extracting ALD-stimulated post-infarct left ventricular (LV) remodeling. Methods and Results-To evaluate the effect of mineralocorticoid receptor antagonist (MRA) spironolactone on post-infarct LV remodeling, 134 patients with first a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
114
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(126 citation statements)
references
References 23 publications
8
114
0
3
Order By: Relevance
“…[236][237][238][239][240][241][242][243][244][245][246][247] Aldosterone blockade by spironolactone was shown to reduce all-cause mortality in adults with symptomatic HF by 35% when it was added to standard HF therapy in the RALES trial (Randomized Aldactone Evaluation Study). 248 Subsequently, eplerenone was found to provide a similar survival benefit in adults with HF caused by LV dysfunction 249,250 In addition to improving survival and hospitalization rates, canrenone and spironolactone have been associated with reverse remodeling in adults with HF.…”
Section: Mineralocorticoid Antagonistsmentioning
confidence: 99%
“…[236][237][238][239][240][241][242][243][244][245][246][247] Aldosterone blockade by spironolactone was shown to reduce all-cause mortality in adults with symptomatic HF by 35% when it was added to standard HF therapy in the RALES trial (Randomized Aldactone Evaluation Study). 248 Subsequently, eplerenone was found to provide a similar survival benefit in adults with HF caused by LV dysfunction 249,250 In addition to improving survival and hospitalization rates, canrenone and spironolactone have been associated with reverse remodeling in adults with HF.…”
Section: Mineralocorticoid Antagonistsmentioning
confidence: 99%
“…Hayashi et al25 investigated the early use of spironolactone immediately post percutaneous transluminal coronary angioplasty in patients with anterior STEMI and showed a reduction in postinfarct LV remodeling when used in combination with an angiotensin‐converting enzyme inhibitor. Recently, the Early Eplerenone Treatment in Patients With Acute ST‐Elevation Myocardial Infarction Without Heart Failure (REMINDER) trial investigated the effect of initiating oral eplerenone therapy 12 to 24 hours following STEMI admission (in the absence of HF) and reduced the incidence of patients with elevated serum brain natriuretic peptide/N‐terminal‐pro‐brain natriuretic peptide at ≥1 month after randomization, when compared with placebo 40.…”
Section: Discussionmentioning
confidence: 99%
“…Patients randomized to MRA therapy will receive an intravenous bolus of potassium canrenoate (200 mg, in keeping with the dose used initially by Hayashi et al25 and subsequently in the Aldosterone Blockade Early After Acute Myocardial Infarction [ ALBATROSS ] trial)26 followed by oral spironolactone 25 mg once daily for 2 weeks and then 50 mg once daily for the remaining 10 weeks, after which the MRA therapy will be stopped. Serum K + will be checked at 2 and 4 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Although American College of Cardiology/American Heart Association/European Society of Cardiology guidelines recommend preoperative administration of β-blockers and amiodarone to prevent POAF, 7 no such guidelines have been developed in Japan and there have been no reports about angiotensin receptor antagonist or aldosterone blockers. It was reported that aldosterone blockers can prevent exacerbation of heart failure and cardiac fibrosis, [21][22][23] and Swedberg et al 24 recently demonstrated that the aldosterone blocker eplerenone decreased AF by 42% in patients with heart ACEi indicates angiotensin-converting enzyme inhibitor; ARB, angiotensin receptor blocker; COPD, chronic obstructive pulmonary disease; and PAD, peripheral arterial disease. failure.…”
Section: Discussionmentioning
confidence: 99%